2014
DOI: 10.1063/1.4869716
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillar instability of a two-dimensional viscoelastic planar liquid sheet in surrounding gas

Abstract: A two-dimensional viscoelastic planar liquid sheet subjected to a considerable temperature gradient perpendicular to the surfaces, moving in a gas medium, was investigated in a linear scope. The sheet instability was explored by solving the dispersion relation in the sinuous mode. Results suggested that the viscoelastic liquid sheet could behave with greater stability than its Newtonian counterpart when the temperature difference was sufficiently large. Thermal effects improved sheet instability, while the liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…This indicates that the antisymmetric disturbances always prevail over symmetric disturbances for non-Newtonian liquid sheets. The same conclusion has been obtained by many investigations (Bird, 1976;Pearson, 1976;Liu and Liu, 2008;Yang et al, 2010Yang et al, , 2012cTong et al, 2014).…”
Section: Introductionsupporting
confidence: 88%
“…This indicates that the antisymmetric disturbances always prevail over symmetric disturbances for non-Newtonian liquid sheets. The same conclusion has been obtained by many investigations (Bird, 1976;Pearson, 1976;Liu and Liu, 2008;Yang et al, 2010Yang et al, , 2012cTong et al, 2014).…”
Section: Introductionsupporting
confidence: 88%
“…The results suggest that the Prandtl number is a stabilizing factor, causing the annular liquid jet to be more stable when Re = 0.5. Meanwhile, similar to the results of Tong et al [22], increasing the Prandtl number has no impact on the unstable growth rate in the case Ma = 0. However, when Re = 5, as shown in Figure 8, increasing the Prandtl number enhances the instability.…”
Section: Effect Of Prandtl Numbersupporting
confidence: 88%
“…They found that the liquid sheet becomes more unstable when a temperature difference exists, and liquid viscosity destabilizes the sheet under this condition. Following their study, Tong et al [22] investigated the thermocapillary instability behavior of planar liquid sheets when the elastic effect was introduced. The spatial-temporal instability behavior of a viscous liquid sheet with a temperature difference between the two surfaces was investigated theoretically [23].…”
Section: Introductionmentioning
confidence: 99%
“…By solving the dispersion equation numerically, it can be found that the liquid jet tends to become unstable when the minimum value of disturbance growth rate is positive. 2329 In supercritical cases, the linear stability analysis method fails to accurately predict the stability of electrified jets. Due to the disappearance of surface tension, which forces the Weber number tends to infinity, the supercritical regime is exceedingly complicated.…”
Section: Methodsmentioning
confidence: 99%